PENGARUH GREEN TRUST, GREEN SATISFACTION, DAN PERCEIVED VALUE TERHADAP REPURCHASE INTENTION (Studi Kasus: Generasi Z Pengguna Produk The Body Shop di Kota Jakarta) - Nakhla, Azliya; Nugroho, Mochammad Noviadi; Suhyanto, Otong (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Generation Z's concern for environmental sustainability is undeniable. The skincare and cosmetics sector in Indonesia has adopted green marketing strategies in response to this. One of the stores is The Body Shop companies that frequently uses this strategy. This study analyzes the effects of perceived value, green trust, and green satisfaction on repurchase intent among Generation Z consumers in Jakarta. A quantitative methodology was used to gather data from 100 specially chosen participants who completed an online survey. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique was employed to examine the data. The outcomes demonstrate that the three variables have a considerable and favorable impact on repurchase intention, both separately and in combination. According to these findings, marketing strategies should be in line with sustainability ideals in order to increase consumer loyalty among Generation Z, who prioritize ethics and environmental responsibility while making decisions.